PERTANGGUNGJAWABAN NOTARIS TERHADAP PELANGGARAN KODE ETIK TERKAIT PEMALSUAN AKTA OTENTIK - Serena, Michelle Audrey; Saly, Jeane Neltje; Sugiarto, Ivan Richard; Rambu, Regina Victoria; Wisuta, Ris; Pasyah, Rabbil Arya; Yulianto, Hermawan (Peneliti.net, 2023)
This study aims to examine the violation of the code of ethics of a notary who falsifies the authentic code. By using normative research methods, it can be concluded: Notary is a profession that has been appointed by the government in terms of making authentic deeds that have been regulated in law, notary also has authority in terms of agreements. The deed made by a notary must meet the requirements so that it can be considered or called a deed that has authentic characteristics, if in the process of making an authentic deed it is not structured and does not meet the requirements then the deed can be canceled in the eyes of the law. However, thus there are still many notaries who commit acts of fraud and negligent actions regarding the profession they carry out. The government and related institutions must work together to increase awareness of the importance of securing legal documents and implement appropriate measures to deal with counterfeiting of authentic deeds.